2016
DOI: 10.3310/hta20940
|View full text |Cite
|
Sign up to set email alerts
|

The use of fibrin sealant during non-emergency surgery: a systematic review of evidence of benefits and harms

Abstract: BackgroundFibrin sealants are used in different types of surgery to prevent the accumulation of post-operative fluid (seroma) or blood (haematoma) or to arrest haemorrhage (bleeding). However, there is uncertainty around the benefits and harms of fibrin sealant use.ObjectivesTo systematically review the evidence on the benefits and harms of fibrin sealants in non-emergency surgery in adults.Data sourcesElectronic databases [MEDLINE, EMBASE and The Cochrane Library (including the Cochrane Database of Systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 213 publications
0
19
0
Order By: Relevance
“…The role of fibrin glue in elective surgery was assessed recently in a systematic review and meta‐analysis. This excluded all studies included in the present review as burn injuries did not meet the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of fibrin glue in elective surgery was assessed recently in a systematic review and meta‐analysis. This excluded all studies included in the present review as burn injuries did not meet the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A significant safety concern was raised regarding air embolism with fibrin glue spray delivery systems. However, the European Medical Agency concluded that the benefits outweighed the risks. Furthermore, this complication was seen predominantly in intra‐abdominal or vascular surgery and is unlikely to arise in skin grafting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, few adverse outcomes of fibrin sealants have been reported and the majority of trials found no harm related to their use 26. Intravascular application with subsequent thrombosis or gas embolism in the case of spray usage, allergic reactions, poor wound healing and infections account for possible and reported harms of sealants.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, these agents are used in confined places and can then lead to compression of surrounding structures. Many of the complications associated with these agents are related to surgical uses rather than emergency department applications [39].…”
Section: Adverse Effects and Complications Of Topical Hemostatic Agentsmentioning
confidence: 99%